Cloning and expression of antibody fragment (Fab) II: Effect of expression hosts on light and heavy chain gene expression - Mehta, Deepa; Chirmade, Tejas; Nainwal, Neeraj; Bhambure, Rahul (Biochemical Engineering Journal, 2023)
Protein expression stoichiometry of individual subunits plays a critical role in the formation of multi-domain functional therapeutic proteins like antibody fragments. In this study, we have evaluated light to heavy chain ratio (LC: HC) of rHu Ranibizumab expressed using duet expression vector in six E. coli strains. The LC: HC ratio at the protein level was determined using RP-HPLC whereas transcript abundance of LC and HC at the mRNA level was determined using RTqPCR. Protein level study as well as the transcript abundance profiles of the LC and HC genes were observed to be differentially expressed across the E. coli strains. BL21 STAR (DE3) and Origami 2 strains resulted in a nearly equal expression ratio of LC and HC genes. Untargeted shotgun proteomics analysis was performed to identify the differentially expressed proteins. Total 1083 proteins were identified in the spectral IDA library, while 244 and 149 proteins were differentially expressed in Origami 2 and BL21 STAR (DE3) respectively. These proteins are associated with translation and nucleotide biosynthesis pathways. Ob-tained results provide insights into the impact of different E.coli host strains on LC: HC ratio, the probable reasons behind the unbalanced gene ratio, and provide useful transcriptomic and proteomics analysis protocols.
Keywords: E.coli host strains; Expression stoichiometry; Proteome analysis; rHu biosimilar Ranibizumab; Transcript abundance